Communication satellite antennas : system architecture, technology, and evaluation - Dybdal, Robert (New York : McGraw-Hill, 2009)
A practical approach to antenna technology for communication satellites--from the world expert on the subject
Fundamental parameters -- Technology survey -- Communication satellite system architectures -- Propagation limitations and link performance -- Interference susceptibility and mitigation -- Space segment antenna technology -- User segment antennas -- Antenna test facilities and methodologies -- Satellite antenna system evaluation.
Includes bibliographical references and index.
Keywords: Artificial satellites -- Radio antennas; Satellite dish antennas; Artificial satellites in telecommunication